2013
DOI: 10.5005/jp-journals-10016-1065
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Hyperstimulation Syndrome

Abstract: ART is proven of great help to all the infertile couples anxious to get pregnant , but is not free of side effects and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…When couples must choose ART, at this stage, women are required to undergo hormonal stimulation that they should not experience. Hormonal stimulation is known to have very agonizing effects for a woman’s body, and it can even be life-threatening ( Mahajan, 2013 ). Because of the failure of male reproductive function, women must bear the consequences.…”
Section: Discussionmentioning
confidence: 99%
“…When couples must choose ART, at this stage, women are required to undergo hormonal stimulation that they should not experience. Hormonal stimulation is known to have very agonizing effects for a woman’s body, and it can even be life-threatening ( Mahajan, 2013 ). Because of the failure of male reproductive function, women must bear the consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a lower basic LH/FSH ratio at the beginning of the COH process in SOR patients compared with the control group (basic LH/FSH ratio in ultra-long/long protocol, LH/FSH ratio on COH day 2 in antagonist protocol, respectively). A small section of the population could be more sensitive to downregulation, exhibiting excessive pituitary suppression and insufficient LH levels ( 4 , 15 ). Usually, GnRH agonists inhibit 90% of the LH level but only inhibit about 40%–50% of the FSH level.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, receptor polymorphism inspection is not able to be widely used in clinic because it is time-consuming and money-consuming for most patients; of course, for patients with unexplained refractory SOR, FSH/LH receptor gene polymorphism inspection should be suggested to patients. Half-dose long-acting injection of GnRH-a or even 1/4~1/3 dosage can be considered to prevent excessive suppression of the pituitary gland for some patients with a history of SOR ( 1 , 4 ). When serum LH <1.0 IU/l, the startup time of Gn can be considered for postponement or that LH can be used at the startup time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation